The strengths and weaknesses of social innovation: a comparison between Malaysia and Thailand / Siti Maziah Ab Rahman …[et al.] - Ab Rahman, Siti Maziah; Setapa, Mariam; Abdul Wahab, Mohd Hafeez Al-Amin; Mohd Yasin, Ahmad Bukhari; Tengku Yahya, Tengku Badariah; Sazali, Nur Ain (Universiti Teknologi MARA, 2021)
Innovation is important in enhancing the country's competitiveness and contributing to knowledge-based urban development. The development of innovation that focuses only on the economic perspective leads to the imbalance of development when there is a gap in economic growth and social development of society. The emergence of social innovation is a complement to corporate innovation that focuses only on profit. Thus, this article aims to highlight the strengths and weaknesses of social innovation in two countries which is Malaysia and Thailand. The findings show that both governments of Thailand and Malaysia have taken the social innovations initiative as a serious matter by incorporating it as one important agenda in their economic planning and framework. However, besides of success stories discussed in this paper, there are also some weaknesses point out in this paper need to address seriously by the respected parties.